Regional Poverty within the Rich Countries - David Jesuit; Lee Rainwater; Timothy Smeeding (Luxembourg Income Study (LIS), 2002)
Using regional incomes as the reference group, disposable income poverty rates are computed for the two most recent waves of Luxembourg Income Study (LIS) data available for the following countries: Australia, Canada, Finland, France, Germany, Italy, the United Kingdom, and the United States. In addition, we aggregate the regions of the five western European countries we examine so that we can better assess the effectiveness of Europe's efforts to reduce the economic gaps between regions. We find that the countries we examine have patterns of regional poverty that help us better understand the national aggregate measures, and we are able identify areas where antipoverty efforts should be made a priority.
Keywords: 330; Armut; Regionale Disparität; Australien; Deutschland; Finnland; Frankreich; Großbritannien; Italien; Kanada; USA